A intera????o entre escola e comunidade na forma????o cultural: um estudo da experi??ncia educativa na Escola Estadual de S??o Paulo - E.E. Dona Am??lia de Ara??jo. Anos de 2013 a 2015 - Souza, Roseli Trevisan Marques de (2015)
It is a qualitative research, in the case study, and carried out by a participant observation, with interviews and document analysis, a philosophical-educational approach the critical nature. It aims the social interaction in the educational experience at School Dona Amelia de Ara??jo, in order to evaluate its contribution to the cultural background of their students. Regarding the finding that the interaction between school itself and schools and the communities, usually, cannot ensure to the students significant cultural education, which is effectively a mediator of social inclusion, and the objective is to demonstrate the hypothesis that the educational experience of that school itself, by engaging activities of school/community interaction in its pedagogic-political project has provided a far-reaching cultural education related to social education. So it aims to characterize and analyze critically this experience and develop a critical thinking about it, using theories from Lib??neo, Severino, Giroux and Goffman. And applying methodological procedures of field research, by carrying out participant observation, interviews, document analysis and theoretical research in bibliographical sources. The result includes the presentation of a state school in the state of S??o Paulo that gradually builds a model of interaction school/school and school/community with fruitful inclusive educational activities, structuring, this perspective of work, a consolidated learning by the idea of democracy and the exercise citizenship.